2006
DOI: 10.1093/jee/99.2.253
|View full text |Cite
|
Sign up to set email alerts
|

A Survey of Pesticide Residues in Pollen Loads Collected by Honey Bees in France

Abstract: In 2002, a field survey was initiated on French apiaries to monitor weakness of honey bee, Apis mellifera L., colonies. Apiaries were evenly distributed in five sites located on continental France. Five colonies were randomly selected in each apiary, leading to a total of 125 studied honey bee colonies. For 3 yr (starting in autumn 2002), colonies were visited four times per year: after winter, before summer, during summer, and before winter. Pollen loads from traps were collected at each visit. Multiresidue a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
137
1
8

Year Published

2010
2010
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 243 publications
(155 citation statements)
references
References 24 publications
9
137
1
8
Order By: Relevance
“…Increased probability of Nosema infection was reported in bees that consumed pollen with a higher fungicide load (Pettis, Lichtenberg, Andree, Stitzinger, & Rose, 2013). Likewise, the residues of insecticide imidacloprid in nectar and pollen at high levels may be dangerous to bees (Laurent & Rathahao, 2003;Chauzat et al, 2006). Widespread losses of colonies in France is due to imidacloprid (Laurent & Rathahao, 2003).…”
Section: Pesticidesmentioning
confidence: 99%
See 1 more Smart Citation
“…Increased probability of Nosema infection was reported in bees that consumed pollen with a higher fungicide load (Pettis, Lichtenberg, Andree, Stitzinger, & Rose, 2013). Likewise, the residues of insecticide imidacloprid in nectar and pollen at high levels may be dangerous to bees (Laurent & Rathahao, 2003;Chauzat et al, 2006). Widespread losses of colonies in France is due to imidacloprid (Laurent & Rathahao, 2003).…”
Section: Pesticidesmentioning
confidence: 99%
“…Similarly, other pesticides "acaricides" have also been found harmful for bees' health (Harz, Muller, & Rademacher, 2010). The acaricidal substances that were intentionally brought into the hives to control V. destructor are the most reported pesticides residues in honey bee colonies (Chauzat et al, 2006;Mullin et al, 2010;Johnson, Ellis, Mulli, & Frazier, 2010;Bernal et al, 2010). In most of the cases, the major pesticide contaminants in hives are the ones used by beekeepers and their residues have shown a number of sub lethal effects.…”
Section: Pesticidesmentioning
confidence: 99%
“…Imidacloprid residues have been found at concentrations of up to 13 ng in sunflower plants (Laurent & Rathahao, 2003). Chauzat et al (2006) identified 36 different types of residues in pollen loads in apiaries of France. Imidacloprid was the most frequently found compound (49.4%), followed by 6-chloronicotinic acid (44.4%) and fipronil (12.4%) in the analyzed samples.…”
Section: Introductionmentioning
confidence: 99%
“…However, the persistence of OCP residues in flowers, plants, soil, and water previously treated with OCPs constitutes a form of environmental contamination; thus, bees can encounter these chemicals and carry them back to their hives [6]. As a consequence, some papers have reported the presence of OCPs in honey [9]; in addition, Chauzat and co-workers [10] have reported the presence of endosulfan, an OCP, in pollen loads. Furthermore, pollen and other bee products can be contaminated directly as a result of the chemical treatment of hives against bee pests [6].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, two methodologies have been reported for the analysis of imidacloprid and its metabolites [21,22]. Just two papers on the development of methods for the analysis of complex mixtures of pesticides and veterinary drugs were found in the literature [10,23].…”
Section: Introductionmentioning
confidence: 99%